2017
DOI: 10.1093/heapro/dax075
|View full text |Cite
|
Sign up to set email alerts
|

Rangatahi Tū Rangatira: innovative health promotion in Aotearoa New Zealand

Abstract: Rangatahi Tū Rangatira (R2R) is a national health promotion programme in Aotearoa New Zealand which aims to promote cultural and physical wellbeing for rangatahi (young people) and their whānau (family). Grounded in tikanga Māori, the programme focuses on total wellbeing, leadership and cultural awareness providing rangatahi opportunities to increase their participation in physical activity and cultural knowledge through ngā taonga tākaro (Māori ancestral games). This paper focuses on an evaluation of this inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The corresponding authors of all 27 studies were contacted; 21 authors replied. From these, 15 of the 21 studies confirmed they included a YPAG [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] ; the remaining 6 either did not use a YPAG (n=3) [28][29][30] or had YPAG members who were all aged over 18 years (n=3). 31,32,33 For the six studies where authors did not respond, we assumed a YPAG was used based on information provided in the paper.…”
Section: Identifying and Quantifying Ypag Reportingmentioning
confidence: 99%
“…The corresponding authors of all 27 studies were contacted; 21 authors replied. From these, 15 of the 21 studies confirmed they included a YPAG [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] ; the remaining 6 either did not use a YPAG (n=3) [28][29][30] or had YPAG members who were all aged over 18 years (n=3). 31,32,33 For the six studies where authors did not respond, we assumed a YPAG was used based on information provided in the paper.…”
Section: Identifying and Quantifying Ypag Reportingmentioning
confidence: 99%
“…Aotearoa is a bicultural nation with a commitment to achieving equitable health and education outcomes for all, particularly for Māori, the Indigenous people of Aotearoa (Kenzie‐Jones, 2019; Nikolakis et al, 2019). Connections between ethnicity, education and health are well documented, (Durie, 2011; Severinsen & Reweti, 2019), despite this, the standard approach to mental ill‐health is built on western political, social and cultural systems that inadequately acknowledge relationships, meaning, values, beliefs and cultural practices that are critically important to Māori (Rangihuna et al, 2018). Acknowledgment of the potential for cultural mismatch, when importing an initiative from overseas, was acknowledged in the context of different break‐time expectations between schools in the US and Aotearoa as well as customs and practices specific to Māori culture that were important to acknowledge and embed in any initiative delivered in the Aotearoa context.…”
Section: Introductionmentioning
confidence: 99%